THE ANALYSTS OF RELIGIOSITY AND EMOTIONAL INTELLIGENCE TOWARDS ATTITUDE IN EDUCATION DURING COVID-19 PANDEMIC - Mohd Nazrul Azizi; Zahari Ishak; Firdaus Hilmi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The holistic approach to education – that addresses students’ learning, social and emotional, and spiritual needs – is crucial, especially in times of crisis. University closures related to the current COVID-19 pandemic mean that students from diverse backgrounds who are more at risk of increased vulnerability are less likely to receive the support and extra services they need, and the gap between students that experience additional barriers and that do not might widen. The current study investigates the influence of religiosity and Emotional Intelligent on the attitude towards leadership in education during pandemic covid-19 in the Malaysian context. Data were collected from undergraduate students who constitute future leaders. Results from the regression analysis particularly the relative weight analysis revealed that leadership practices demonstrated significant incremental variance with attitude towards leadership beyond self-leadership. The implications of the findings for research and practice are discussed.